Being rational about (im)precision: a statement from the Biochemistry Subcommittee of the Joint European Society of Cardiology/American College of Cardiology Foundation/American Heart Association/World Heart Federation Task Force for the Definition of Myocardial Infarction - Jaffe, Allan S.; Apple, Fred S; Morrow, David A; Lindahl, Bertil; Katus, Hugo (Clinical chemistry, 2010)
We have for many years advocated for very precise cardiac troponin assays to improve the sensitivity of detection of cardiac necrosis and to decrease over time the amount of change (or delta) in cardiac troponin concentrations needed to be considered significant (1)(2). During the time period when assays were insufficiently precise at very low levels, we and others advocated using as a cutoff concentration the lowest value at which the assay achieved a 10% CV rather than the 99th percentile value (3). Guidelines have never made such a recommendation, however, but instead have promoted recognition that “optimal” diagnostic performance of troponin assays was achieved by using the 99th percentile (1)(4). Over time, assay precision has improved substantially. Nevertheless, some clinicians, as well as some regulatory agencies and clinical trial groups, advocate that troponin assays that fail to meet the 10% CV criterion should not be used. This recommendation is based on the mistaken impression that such assays would increase the rates of false-positive results. This issue is a major concern for clinicians because many cardiac troponin increases are difficult to explain, and thus their detection is often considered a false-positives result. However, increases of troponin, albeit often caused by ischemia, also can be induced by nonischemic cardiac injuries such as those associated with drugs, toxins, and trauma (5).